IDENTIFIKASI NYERI NEUROPATIK DENGAN MEMAKAI SKALA NYERI LEEDS ASSESMENT OF NEUROPATHIC SYMPTOMS AND SIGNS LANSS PADA PENDERITA NYERI PUNGGUNG BAWAH KRONIK - Moya Dewi Marlenny*, Yuneldi Anwar*, Hasan Sjahrir* (NEURONA, 2010)
INTRODUCTION LOW BACK PAIN LBP IS ONE OF THE MOST COMMON PAIN CONDITIONS WHERE NOCICEPTIVE AND NEUROPATHIC COMPONENTS BOTH CONTRIBUTE TO PAIN LITTLE INFORMATION IS AVAILABLE ABOUT THE CONTRIBUTION OF THE NEUROPATHIC COMPONENT TO LBP